How to create an independent research program - Krieger, Melanie Jacobs, 1944- (Association for Supervision and Curriculum Development, 1999)
Give students at your school a chance to engage in exciting research projects by creating your own independent research program. This guide explains every step, from getting sponsors to recruiting students and entering research papers into national competitions.